2013
DOI: 10.1590/s1516-05722013000300015
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da atividade antiedematogênica, antimicrobiana e mutagênica das sementes de Amburana cearensis (A. C. Smith) (Imburana-de-cheiro)

Abstract: RESUMO:Foram avaliados os efeitos antiinflamatório, antibacteriano e mutagênico do extrato aquoso das sementes de Amburana cearensis. A atividade antiinflamatória foi avaliada em modelo de edema de pata induzido por carragenina, utilizando o extrato em concentrações de 10 % e 20 % nos grupos experimentais; AAS 10 mg/kg (v.o) no grupo padrão e água destilada no grupo controle. A atividade antimicrobiana foi determinada através do método de diluição em Agar, utilizando concentrações de extrato de 10 %, 7,5 %, 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
0
5
0
8
Order By: Relevance
“…Possivelmente, essa resposta é positiva para os animais aos 14 dias. Segundo Lima et al (40) , os eosinófilos têm participação em reações alérgicas e na resposta aguda inflamatória, podendo induzir dano tecidual (eosinofilia). Estas células migram da circulação para os locais de infecção e inflamação, onde são importantes contra infecções por parasitas e/ou alergenos.…”
Section: Resultsunclassified
“…Possivelmente, essa resposta é positiva para os animais aos 14 dias. Segundo Lima et al (40) , os eosinófilos têm participação em reações alérgicas e na resposta aguda inflamatória, podendo induzir dano tecidual (eosinofilia). Estas células migram da circulação para os locais de infecção e inflamação, onde são importantes contra infecções por parasitas e/ou alergenos.…”
Section: Resultsunclassified
“…There is no report of antibacterial activity in A. cearensis seeds extracts prior to this work. Santos et al (2010) have shown activity of peptide from A. cearensis seeds only against phytopathogenic fungi and yeasts and Lima et al (2013) showed no antibacterial activity against strains of S. aureus, E. coli and P. aeruginosa with their A. cearensis extract. Catechin and naringin is present in EEA extract (Table 2), it is known that these phenolic compounds act against microorganisms (Anand and Rai, 2016), then it explains the antimicrobial activity of this extract.…”
Section: Antibacterial Assaymentioning
confidence: 98%
“…Several studies have demonstrated the presence of secondary metabolites and antimicrobial activity in leaves and stem bark of the A. cearensis, however, the seeds do not present similar results (Lima et al, 2013), this is already expected because the main constituents of most seeds are carbohydrates, lipids and proteins, followed by other constituents in smaller amounts such as vitamins, minerals and water (Vaclavik and Christian, 2006). Furthermore, the solubility of secondary compounds depends on the type of solvent used, degree of polymerization, as well as interaction with other food constituents and formation of insoluble complexes (Naczk and Shahidi, 2004), indicating the need for further studies with this part of the plant.…”
Section: Introductionmentioning
confidence: 97%
“…São inúmeras as plantas utilizadas com finalidade terapêutica; no entanto, a maioria das espécies não foi totalmente estudada, principalmente no que diz respeito aos seus compostos com efeitos citotóxicos, mutagênicos ou genotóxicos, os quais podem gerar danos à saúde humana 6 . Uma planta muito utilizada pela população como medicamento natural é a Synadenium grantii Hook.…”
Section: Introductionunclassified